(untitled) (Journal of Science Foundation, 2013)
Background: The physiological conditions of fish are essential for the successful fish culture. Objective: The purpose of the present study was to see the haematological parameter of air breathing cat fish (Heteropneustes fossilis) of Bangladesh. Methodology: This animal study was conducted in the Bargen lab in the Department of Zoology at University of Dhaka as well as in The Peoples Pathological lab which was a private diagnostic laboratory at Dhaka city from July 2008 to April 2009 for a period of 9(nine) months. The fish was Heteropneustes fossilis. Haemocytometer including two graduated pipettes was used for counting leucocytes. Result: The result indicated eight types of blood cells in peripheral condition of Heteropneustes fossilis. The average cellular counts of Heteropneustes fossilis were erythrocytes 8.45´106 m3, leukocytes 15.44´103m-3, Thrombocytes 34.72%, large lymphocytes 1.02%, small lymphocytes 26.7%, monocyte 3.9%, neutrophil 16.9%, eosinophils 6.97%, basophiles 8.6%, haemoglobin 11.7g 100ml1, erythrocyte sedimentation rate (ESR) 6.49g 100ml-1. The most of the hematological parameter showed intra specific variation except eosinophils and ESR of Heteropneustes fossilis (Shing fish). Conclusion: Hematological studies shows that the physiology of fish change with the change in the environment, time, season, maturity, nutritional state, activity level physical and chemical change in water. DOI: http://dx.doi.org/10.3329/jsf.v11i1.19398